Holy brothers geography, kinship, and priesthood in ancient Israel - Rasure, Matthew R. 1981- (Lanham Lexington Books/Fortress Academic, 2024)
"Through the lenses of geography, kinship, and priesthood, this book brings into focus varied biblical materials related to Israel's early priesthood. With the tools of Documentarian narrative analysis and literary genealogies, Matthew R. Rasure delves deep into the memories of Aaron and Moses and the invention of their brotherhood"--
Includes bibliographical references and index
Keywords: Bible -- Historiography; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Priests, Jewish -- History; Priests, Jewish -- Biblical teaching; Jews -- History -- To 586 B.C; Genealogy in the Bible